Neuroendocrine Carcinomas of the Gallbladder: A Clinicopathologic and Immunohistochemical Analysis of 34 Resected Cases. (October 2020) - Lee, Sun Mi; Sung, Chang Ohk
Abstract : Neuroendocrine carcinoma (NEC) is an aggressive malignant tumor that rarely arises from the gallbladder. Here, we investigated the clinicopathologic and immunohistochemical characteristics of 34 NECs of the gallbladder. The patients were predominantly women (68%) with a median age of 63 years (range, 37 to 82 y). NECs frequently occurred in the fundus (44%) as mass-forming lesions (66%). Histologically, 17 tumors were of small cell type, and another 17 were of large cell type. Twenty-three cases (68%) were associated with biliary intraepithelial neoplasia (38%) and intracholecystic papillary neoplasm (29%). The majority of tumors exhibited a diffuse growth pattern (74%), followed by organoid (24%) or scirrhous (2%) growth patterns. Histologic features related to neuroendocrine differentiation, such as nuclear molding (56%), perilobular pseudopalisading (18%), and rosette formation (15%), were identified. Immunohistochemically, cytokeratin 7 and 20 were expressed in 19 (56%) and 8 (24%) cases, respectively. Loss of Rb1 expression and concomitant overexpression of p16 were observed in 25 (74%) cases. No BRAF V600E mutations were identified in any of the 34 NECs. For survival analysis, the 1-, 3-, and 5-year overall survival rates were 64%, 35%, and 19%, respectively. In a multivariate analysis, the receipt of adjuvant chemoradiation therapy was identified as the only independent prognostic factor associated with the overall survival rate. The 1- and 3-year overall survival rates of patients with NECs were poorer for patients with poorly differentiated adenocarcinoma of the gallbladder ( P <0.001). The complete resection and application of postoperative adjuvant therapy may influence a better clinical outcome in patients with NEC of the gallbladder.